2010
DOI: 10.1021/ja1015266
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidation of Tyrosine by Parallel Rate-Limiting Proton Transfer and Multisite Electron−Proton Transfer

Abstract: We report here corrected values for k -1 for back proton transfer in the mechanism in Scheme 1. The initial values did not include the total concentration of tyrosine in the calculated rate constants. We also report a corrected value for k red . The corrected Table 1 is given here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…Similar investigations have been carried out with the proton acceptor dispersed in nonaqueous (17,18) or aqueous (19,20) solutions.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…Similar investigations have been carried out with the proton acceptor dispersed in nonaqueous (17,18) or aqueous (19,20) solutions.…”
mentioning
confidence: 66%
“…We used the clever implementation of the method proposed in ref. 41, which uses an indium-tin-oxide electrode, prepared as described in SI Appendix, that slows down the direct oxidation of phenol at the electrode and makes the catalytic enhancement of the current more apparent. The value found for the rate constant, k þ ¼ 3 × 10 5 M −1 s −1 , confirms the photochemical result, which may, however, be considered as more accurate in view of the remaining overlap between catalytic current and direct oxidation current in the redox catalytic technique.…”
Section: Resultsmentioning
confidence: 99%
“…An example is shown in Eq. 6 with HPO 4 2− as the proton acceptor base (20,21 The appearance of a base-dependent pathway in water oxidation suggests a similar microscopic origin with O-atom transfer from ½Ru V ðMebimpyÞðbpyÞðOÞ 3þ to H 2 O accompanied by proton transfer to the added base, Eq. 7.…”
Section: Discussionmentioning
confidence: 95%
“…3 and the rate constants in Table 1 Table 1 also illustrate that k B increases with the proton acceptor ability of the base (ΔG o0 ¼ −RTpK a ). A related effect has been documented for electron-proton transfer oxidation of tyrosine arising from the effect of enhanced basicity on ΔG o0 for the concerted electron-proton transfer step (20,21).…”
Section: ∕2mentioning
confidence: 96%
“…Thorp and Meyer found that the increase of such catalyzed current is proportional to the concentration of phosphate buffer, from which two mechanisms were proposed: electron and proton transfer (EPT) or proton transfer followed by electron transfer (PT-ET) [49,50]. As depicted in Scheme 2D, the formation of ArOH-OP(OH)-O 2 2À initiates two different pathways: electrons and protons were retained jointly (EPT, left) or progressively (PT-ET, right), indicating the possibility of multi-site electroproton transfer [102].…”
Section: Dppz]mentioning
confidence: 99%